OC-014 High definition colonoscopes cause more pain and require more sedation than the standard video endoscope. (28th May 2012) - Lim, Y C; Corbett, G D; Cameron, E; Parkes, M
Abstract : Introduction: It has been anecdotally observed in this centre, a tertiary teaching hospital, that high definition colonoscopes (HDC) seem to be more difficult to manoeuvre and cause more pain to the patient. Although studies have been reported that HDC may have a higher polyp detection rate compared to standard video colonoscopy 1 (SVC) there is very little data on the tolerability and comfort of HDC. To our knowledge this is the first study to assess the tolerability of HDC against SVC. The colonoscopy score used in this centre is a five point score which is documented by the assisting nurse and used to assess patient experience.  No pain  1 or 2 Episodes of mild discomfort  2 or More episodes of discomfort  Significant discomfort  Extreme discomfort. Methods: All colonoscopies between 1 April 2010 and 31 March 2011 were identified from the endoscopy database and the reports were retrieved and reviewed for quality indicators (sedation dosing, caecal intubation and polyp detection). Separate pain score records documented by the endoscopy nurses were also retrieved. When analysing the pain score, it was divided into two groups (1 and 2 vs 3, 4 and 5) as a score of 3 and above describes markedly worse pain for the patient. These results were analysed for significance using appropriate statistical tests (Fishers and Mann–Whitney U). Results: A total of 4401 colonoscopies were performed by 33 endoscopists during the study period. 611 of these were excluded due to incomplete data. Of the remaining 3790 procedures, 902 procedures were performed with HDC and 2888 with SVC. There were no demographic differences between the two groups. 5% more patients had a pain score of 3 or more when using the HDC (p=0.01). Their use was also associated with a marginal but significant increase in the dose of midazolam and fentanyl (p<0.001 and p=0.04 respectively). Polyp detection was significantly lower in the HDC group (p=0.01). The results are shown in Abstract OC-014 table 1 . Conclusion: This is the first study evaluating tolerability of HDC. In this large cohort of patients performed by a large number of endoscopists, tolerability and polyp detection were worse with HDC. Competing interests: None declared. Reference: 1. Subramanian V, Mannath J, Hawkey CJ, et al. High definition colonoscopy vs standard video endoscopy for the detection of colonic polyps: a meta-analysis. Endoscopy 2011;43 :499–505.